THE INTERDEPENDANCE BETWEEN ATTRIBUTIONS AND SECOND LANGUAGE ATTAINMENTS IN SECONDARY SCHOOL STUDENTS - Bogusława Gosiewska-Turek (Journal of Education Culture and Society, 2017)
Affective factors are undoubtedly considered to be vital in second language acquisition. Among these factors attribution theory is of primary significance, as it affects learners’ final achievement. It indicates that people attribute various causes in their lives to their success and failure. With the employment of attribution theory, this study examines Polish secondary school adolescent students’ attributions for success and failure in second language learning. The main purpose of the study is to investigate, whether Polish secondary school students’ attributions have an impact on their achievements in second language acquisition. In order to conduct the study, the researcher administered attribution questionnaires to the students and an achievement sheet to the teacher to fill in with students’ semester grades in English. Then the data obtained from the questionnaires and the achievement sheet were correlated. The results show that successful students are more likely to attribute their success to internal facets such as ability and effort and unsuccessful learners attribute their lack of success to external factors, among which task difficulty or luck could be enumerated.